The Effectiveness of The Critical Incident Method on Learning Outcomes in Qur'an and Hadith Material for Third Grade Students at Madrasah Ibtidaiyah - Azizah, Nurul; Wulansari, Annisa; Anwar, Heru Saiful (Universitas Islam Sultan Agung, 2024)
The purpose of this study was to determine the effect of using the Critical Incident Method on the learning outcomes of the 3rd -grade Qur'an subjects at SDIT Darul Falah Ponorogo. This study uses a quantitative experimental approach with a True Experimental design because the researchers took illustrations as generalizations of the population with a pre-test and post-test control group design approach, the selection of experimental and control classes were selected systematically so that students' abilities were equivalent by using Nonprobability Sampling (Systematic Sampling). . This research took a sample of 30 students who were randomly selected 15 students in the experimental class and 15 students in the control class. In collecting data using tests and documentation, the data technique was tried through the Mann-Whitney non-parametric test because the data were not normally distributed and not homogeneous and were assisted by the SPSS 22 application. The experimental post-test score of 9.93 was greater than the control class post-test score. 9. 2, which means that there is an effect of learning with the Critical Incident method on student learning outcomes which are described by the Mann-Whitney test of 0.05> 0.000. Based on the results of the study, shows that the Critical Incident learning method can be used in various institutions in learning the Qur'an Hadith to make the educational process more creative and innovative, and can be used by other researchers in researching subjects with the same characteristics.